PICTURE WORD INDUCTIVE MODEL BERBASIS SENSORI INTEGRASI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA BERKESULITAN BELAJAR DI SD - Nenden Ineu Herawati, - (2020)
This research is motivated by reading disability of the fourth-grade students, causing them having learning difficulty since reading is the tool to learn other knowledge. The research aims to examine the effectiveness of Sensory Integration-based Picture Word Inductive Model in improving early reading skills of students with learning disabilities in elementary schools. The research employed Research and Development (R&D) method and data analysis of the Wilcoxon test. Research participants were six fourth-grade students in Bandung Regency and Bandung City. The results prove that Sensory Integration-based PWIM can improve early reading skills of the fourth-grade learning disabilities students in elementary schools in Bandung City on the abilities of (1) identifying letters of the alphabet, (2) reading syllables, (3) reading words, and (4) reading simple sentences. The results of the complete test of Sensory Integration-based PWIM learning model on students with learning disabilities using the Wilcoxon test based on SPSS show that the pre-test and post-test scored -4,210. The value which is less than 0,5 means that Sensory Integration-based PWIM can be used to improve early reading skills of learning disabilities students having difficulty in learning to read. The findings recommend that particularly the first-grade elementary teachers and generally all elementary teachers implement Sensory Integration-based PWIM, which functionalizes sensory such as visual, auditory, kinesthetic, touch, and pronunciation, in reading lesson.